Anisotropic field induced phase transitions and negative electrocaloric effect in rhombohedral Mn doped Pb(In1/2Nb1/2)O3-Pb(Mg1/3Nb2/3)O3-PbTiO3 single crystals. Issue 8 (1st June 2018) - Zhou, Yaming; Li, Qiang; Zhuo, Fangping; Yan, Qingfeng; Zhang, Yiling; Chu, Xiangcheng
Abstract: The electrocaloric effect (ECE) of Mn doped Pb(In1/2 Nb1/2 )O3 -Pb(Mg1/3 Nb2/3 )O3 -PbTiO3 (PIN-PMN-PT:Mn) single crystals with particular emphasis on the impact of crystallographic orientations and phase transitions were investigated systematically. Orientation-dependent phase transitions have been demonstrated by the dielectric and strain behaviors. Intriguingly, the negative ECE of – 0.02 °C and – 0.002 °C were obtained firstly in [001]-oriented PIN-PMN-PT:Mn crystals near the rhombohedral→tetragonal phase transformation and in [011]-oriented crystals near the rhombohedral→orthorhombic phase transformation, respectively. However, only the positive ECE was found in [111]-oriented crystals near the tetragonal→rhombohedral phase transition. Additionally, the maximum ECE temperature changes calculated in [001]-, [011]- and [111]-oriented crystals were 0.33 °C, 0.46 °C and 0.38 °C, respectively. Our results suggest that the negative ECE is attributed to electric field-induced phase transitions, whose critical field decreases with the increase of temperature. The phase transition-mediated coexistence of positive and negative effects in the relaxor-ferroelectric single crystals is beneficial to enhance the efficiency of the solid-state cooling devices.